Comparative analysis of ventilatory threshold responses during cycling and treadmill exercise in triathletes - Rajala, Virpi (2025)
Rajala, VJ., 2025. Comparative analysis of ventilatory threshold responses during cycling and treadmill exercise in triathletes. Faculty of Sport and Health Sciences, University of Jyväskylä, Master’s thesis, 42 pages. 2 appendices.